Physicochemical and microstructural properties of composite edible film obtained by complex coacervation between chitosan and whey protein isolate - Tavares, L. (2021)
The aim of this work was to study the potential application of edible films obtained by complex coacervation promoted by the electrostatic interactions between positively charged chitosan (CH) 3% (w/w) and negatively charged whey protein isolate (WPI) 3% (w/w). Preliminary assays of turbidimetry were made in order to find the optimal CH-to-WPI mass ratio for the complex coacervation. The maximum turbidity was obtained in the CH:WPI mass ratio of 0.1:1 (w/w). The dispersions of CH/WPI (both at 3 % (w/w)), WPI 5 % (w/w) and CH 3% (w/w) were analyzed by Cryo-scanning electron microscopy (Cryo-SEM) and the micrograph of CH/WPI coacervate presented a more compact network structure than dispersions of individual biopolymers. The composite CH/WPI films were prepared, characterized and their performance and physicochemical properties were compared with those of CH or WPI films, in terms of water vapor permeability (WVP), mechanical properties, solubility, sorption isotherms, optical properties, scanning electron microscopy (SEM) imaging, Fourier-transform infrared spectroscopy (FTIR) and differential scanning calorimetry (DSC). Results revealed that the incorporation of small amounts of CH in the matrix of WPI led to form a composite film with higher tensile strength, lower deformation, malleability, flexibility, solubility and WVP in comparison to the mono-component WPI and CH films. The CH incorporation resulted in a decrease in equilibrium moisture content of the CH/WPI film and the Guggenheim-Anderson-de Boer (GAB) model of sorption data indicated isotherms of type II. All the films presented a homogeneous structure, color transparency, which is desired in food applications and packaging technology.